The novel relationship between Sirt3 and autophagy in myocardial ischemia–reperfusion. Issue 5 (28th November 2018) - Zheng, Yitian; Shi, Binhao; Ma, Mengqing; Wu, Xiaoqin; Lin, Xianhe
Abstract: Class III histone deacetylases (HDACs) belong to the proteasome family, comprising seven family members identified in mammalian cells, identified Sirt1–Sirt7. As an important member of HDACs, Sirt3 is hotly debated for its multiple functions. It was reported that Sirt3 got involved in the alleviation of multiple diseases, including myocardial infarction, neuron ischemia, hypertrophy, and diabetic myopathy. Through regulating many cellular mechanisms, such as apoptosis, autophagy, and clearance of reactive oxygen species (ROS), Sirt3 played an important role in the alleviation of myocardial ischemia–reperfusion injury. Nowadays Sirt3‐induced autophagy was indicated to be involved in the process of the development of myocardial ischemia–reperfusion injury. Sirt3 could both activate and inhibit autophagy process by activating different downstream signal pathways, such as Sirt3–AMP‐activated protein kinase pathway, Sirt3–Foxo3a pathway, and Sirt3–superoxide dismutase–mitochondrial ROS pathway. Whereas the Sirt3‐induced autophagy in different phases of myocardial ischemia–reperfusion has not been systematically illustrated. In this review, we summarized the regulated mechanisms found in these years and listed the updated research about the relationship between Sirt3 and autophagy which are both positive and negative during myocardial ischemia–reperfusion phase. We anticipated that we may controlled the activation of autophagy by regulating the concentration of Sirt3 in myocyte. By maintaining a proper expression of autophagy in different phases of myocardial ischemia–reperfusion, we could reduce the morbidity of patients with myocardial infarction apparently in the future. Abstract : The signal pathways in Sirt3‐mediated autophagy when myocaridal ischemia–reperfusion (I/R) happened. We tend to find the novel relationship between Sirt3 and autophagy when myocardial I/R happened.